1997
DOI: 10.1530/jrf.0.1090087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with fetal calf serum on development of bovine embryos in synthetic oviduct fluid medium

Abstract: The effects of fetal calf serum (FCS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
2
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 9 publications
5
55
2
3
Order By: Relevance
“…Co-culture systems for mammalian embryos normally contain serum, as much for the benefit of the coculture cells as for possible benefits to the embryos. Addition of serum to the culture medium increases the speed of development manifested in a lack of normal morula compaction and an earlier appearance of the blastocyst [8,23]. This fact is well stated in our results which showed higher Day 6 blastocysts rates in embryos developed with FCS (Groups Vero and FCS), than in the group SOF-BSA.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Co-culture systems for mammalian embryos normally contain serum, as much for the benefit of the coculture cells as for possible benefits to the embryos. Addition of serum to the culture medium increases the speed of development manifested in a lack of normal morula compaction and an earlier appearance of the blastocyst [8,23]. This fact is well stated in our results which showed higher Day 6 blastocysts rates in embryos developed with FCS (Groups Vero and FCS), than in the group SOF-BSA.…”
Section: Discussionsupporting
confidence: 86%
“…The percentage of early embryos that developed to blastocysts is similar for a variety of cells used in co-culture [17,22,23]. Also, it has been shown that when either B2 [38] or TCM199 [17,22,23] were combined with somatic cells in a co-culture system, both media supported a higher rate of development to blastocysts than did control media without cells. Hasler [39], showed that embryos cultured in a B2-BRL coculture exhibited faster development, with a higher total number of blastocysts and more cells than B2 medium without co-culture.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although culture conditions can in¯uence the kinetics of early development (Pinyopummintr and Bavister, 1994;Van Langendonckt et al, 1997), it is likely that the main factors controlling this parameter are intrinsic to the oocyte , the sperm (Eid et al, 1994;Comizzoli et al, 2000;present study) or both. In fact, in mice, a gene controlling the rate of preimplantation cleavage division and subsequent embryo survival (Ped: preimplantation embryo development) has been identi®ed (for review see, Warner et al, 1998).…”
Section: Discussionmentioning
confidence: 97%